Conjugate studies of hydromagnetic waves - Lanzerotti, L.J. (1987)
P(論文) Geophysical studies at conjugate points on the surface of the Earth have played an important role in discovering and elucidating plasma processes in the Earth's magnetosphere. Prof. T. NAGATA has long been an advocate of the importance of conjugate research in studying space phenomena. This review discusses early studies of hydromagnetic waves at conjugate points, including some of the important work of NAGATA and his colleagues and students. This paper also briefly reviews selected important work of the last decade and notes where some advances can be expected in the future at very high and very low latitudes. departmental bulletin paper